Work-related factors of carpal tunnel syndrome in computer users among clerical staffs in government health facilities, Kota Bharu, Kelantan - Ismail, Zaliha; Abdullah, Sarimah; Amin, Mohd lskandar Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
INTRODUCTION: Carpal tunnel syndrome (CTS) is the situation when the median nerve is compressed within the carpal tunnel and causes the signs and symptoms. Uncertainty of local prevalence and failure to eliminate contributory job factors can result in recurrence or progression of CTS symptoms, impaired use of the hand, and the need for surgical treatment. The aim of this study was to determine the prevalence and workrelation associated factors of CTS in computer user among clerical staffs in government health facilities, Kota Bharu, Kelantan. METHODOLOGY: A cross sectional study was carried out at two government health facilities in Kota Bharu, Kelantan, from January until June 2008. Prevalence and workrelated factors of CTS were identified in clerical workers. Exposure to associated factors was assessed by worker's responses on self-administered questionnaire, anthropometric measurement, and direct observation. Disease status was confirmed by history that was suggestive to the syndrome and provocative test performed by a hand surgeon or nerve conduction study. Data was analysed by using simple and multiple logistic regression analyses. RESULTS: A total of300 workers (108 CTS and 192 non-CTS) participated in the study. The prevalence of CTS was 36.0% (95%CI: 31.5, 41.5). The final model included one personal factor - family history of CTS and one work-related time factor - keyboard time (hrs/day). A person with family history of CTS has 9.41 (95%CI: 1.09, 81.65, P value 0.039) times the odds to get CTS as compared to no family history of CTS, and an increase in I hour/day of keyboard time has a 1.11 (95% CI: 1.01, 1.23, P value 0.039) times the odds to have CTS, when adjusted for keyboard time and family history of CTS, respectively. CONCLUSION: The prevalence of carpal tunnel syndrome in computer users was high, indicates high morbidity in this occupation. The relationship of keyboard time and carpal tunnel syndrome showed that carpal tunnel syndrome in computer users was workrelated. Health programmes especially health educations and promotions should be designed based on the factors that influenced the association of carpal tunnel syndrome.